Chemical and sensory properties of single-origin chocolate made from cocoa beans with different fermentation durations - Sunarharum, Wenny Bekti; Wahyuni, Nuril L; Saputro, Arifin D.; Dimas RA, Muhammad; Efrat, Novianus (Hasanuddin University Food Science and Technology Study Program, 2025)
Cocoa is an important agricultural commodity, with global demand rising due to its central role in chocolate production. As the world’s third-largest cocoa producer, Indonesia plays a significant role in the global market, with cocoa beans as an essential export commodity. Recently, single-origin chocolate has gained popularity due to its unique sensory qualities, particularly its aroma and flavor, which are influenced by volatile compounds produced during fermentation. This study investigating the proximate composition, volatile compounds, and aroma profiles of single-origin chocolate derived from cocoa beans subjected to different fermentation treatments or durations: nonfermented/NF, half-fermented/HF (3-day fermentation), and fully fermented/FF (6-day fermentation). The proximate composition of the cocoa beans, nibs, and chocolate products was analyzed, while the chocolate products were further examined for volatile compounds using GC‒MS and sensory aroma profiles through descriptive analysis. The length of the fermentation process affects the chemical and sensory characteristics of single-origin chocolate. Fully fermented cocoa beans and nibs contain the highest fat and protein, along with the least carbohydrates. Chocolate that is unfermented, partially fermented, or fully fermented can be identified by the distinct differences in their volatile compound profiles. These results underscore the critical role of fermentation timing in developing desirable chemical and aromatic characteristics, providing valuable insights for enhancing the production of high-quality single-origin chocolate.